Assessment of consumers’ knowledge, attitude and perception of the impact of the COVID-19 pandemic on household food security in Caribbean Small Island Developing States - Daley, Oral; Roopnarine, Ronald; Isaac, Wendy-Ann P.; Palmer, Donald; John, Afiya; Webb, Marquitta; Dalrymple, Nequesha; Maharaj, Omardath (Frontiers in Sustainable Food Systems, 2023)
The COVID-19 pandemic and recent international crises including the Russia-Ukraine conflict have resulted in significant disruptions along multiple segments of the Caribbean's agri-food system thus compromising regional food security. These impacts are still ongoing with the potential to worsen. The aim of this study was to investigate the influence of sociodemographic factors on consumers' knowledge of food security along with their attitude, and perception towards the impact of the COVID-19 pandemic on household food security in the Caribbean Small Island Developing States. A cross-sectional on-line survey was conducted between January 1 and November 30, 2021. The sampled population included consumers from nine Caribbean countries (Trinidad and Tobago,